# How do you simplify #(0.10 x 10^5)(4.9 x 10^-2)#?

It is easiest if you multiply the coefficients together and then the exponents (and finally normalize).

By signing up, you agree to our Terms of Service and Privacy Policy

To simplify ((0.10 \times 10^5)(4.9 \times 10^{-2})), first perform the multiplication:

(0.10 \times 4.9 = 0.49)

Then, multiply the powers of 10:

(10^5 \times 10^{-2} = 10^{5-2} = 10^3)

So, ((0.10 \times 10^5)(4.9 \times 10^{-2}) = 0.49 \times 10^3 = 490).

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7